Finite local nearrings with split metacyclic additive group - Raievska, I.I.; Raievska, M.I.; Sysak, Y.P. (Algebra and Discrete Mathematics, 2016)
In the paper the split metacyclic groups which are the additive groups of finite local nearrings are classified